Traumatic dental injuries in children and adolescents presenting to a tertiary children’s hospital in Shenzhen, China - Yuanyuan Wang; Huihui Chang; Chanchan Chen; Xin Yang; Ming Quan; Xinmin Liao; Zhiqing Liao (BMC Oral Health)
Abstract Background/Aim Traumatic dental injuries (TDIs) are a significant public health concern, particularly among children and adolescents. The aim of this study was to analyse the characteristics of TDIs and investigate the factors affecting delays in seeking medical care using data from patients treated at Shenzhen Children’s Hospital from January to December 2023. Methods We reviewed the electronic records of 1,683 patients, classifying TDIs into fracture and luxation injuries according to IADT guidelines. Data were analysed via descriptive statistics and multinomial logistic regression to determine demographic and clinical features. Results TDIs were more prevalent in children aged 2–4 years and 7–9 years, with males comprising 70.4% of the patients. The most affected teeth were maxillary incisors. Luxation injuries were more common in primary dentition, whereas fracture injuries were more prevalent in permanent dentition. Additionally, sunny weather and temperatures between 20 °C and 30 °C were identified as risk factors associated with a higher incidence of TDIs. Most patients (98.1%) sought care within 24 h, with age and type of injury significantly influencing the time to treatment. Conclusions Necessary improvements should be considered in the healthcare education system to address dental trauma better. This process is crucial to increase awareness of the importance of timely medical care, both for younger children and their parents.